On dynamics of viscoelastic multidimensional medium with variable boundary - V. P. Orlov (Abstract and Applied Analysis)
We prove the existence and uniqueness theorems for solutions of an initial-boundary value problem to the system of equations, which describes dynamics of viscoelastic continuous medium with a variable boundary and a memory along the trajectories of particles in classes of summable functions.